The relationship of crime and oil development in the coastal regions of Louisiana - Luthra, Asha D. (2006)
This project examines the relationship between patterns of crime and the development of the oil and gas extraction industry in the coastal regions of Louisiana. The suggestion of a link between these phenomena has often been made, but little systematic research has been conducted to determine if there is indeed a crime-oil development nexus. Limited previous research has focused primarily on the issue of “boom and bust” cycles on some forms of deviant behavior, but the data and the methods used were inadequate, and thus, the resulting conclusions were often misleading or possibly erroneous. During the course of this project, a comprehensive database is constructed that facilitates a longitudinal analysis of concomitant variation in crime patterns and oil extraction activity. Annual crime data are obtained at the parish and county level for all years beginning in 1974 and merged with corresponding social and economic data. This dataset allows for a multivariate pooled time series analysis, with adequate controls, to determine the degree of influence between oil activity and crime patterns. The results from the analysis suggest that changes in oil activity and high levels of labor market involvement in the offshore oil industry are not strongly associated with community disruption in the form of crime. The only statistically significant effects due to changes in oil activity are decreased levels of homicide and aggravated assault. Oil development is not associated with any other crime in the analysis despite accounting for the boom and bust cycles of the oil industry over a 25 year period for 12 parishes that are highly involved in the industry. As the industry becomes more active and undergoes an increased labor demand, incidents of homicide and assault decline in the community. This finding does not support some previous boomtown model research that argues that energy development causes higher rates of social disruption, including higher crime rates (Seydlitz et al. 1993a; Brookshire and D’Arge 1980; Dixon 1978; Finsterbusch 1982; Freudenburg and Jones 1991; Gramling and Brabant 1986)